PRIMEIRAS REFLEXÕES SOBRE A PAZ POR MEIO DO DIREITO INTERNACIONAL: CONEXÕES ENTRE DIREITOS HUMANOS E DEMOCRACIA - Santos, Ariana B. d.; Sulzbach, Camila C.; Vieira, Gustavo O. (Salão do Conhecimento, 2013)
Resumo